Integrated Thematic Learning through Contextual Learning to Improve Performance of Students with Mild Intellectual Disability - Kasiyati Kasiyati; Zulmiyetri Zulmiyetri (Journal of Educational and Learning Studies, 2018)
This study aims to determine the effect of integrated thematic instructional, through contextual learning model, for improving performance of students with mild intellectual disability. This research uses classroom action research (Action Research), included collaboration with classroom teachers. The subjects of this research are four students with mild intellectual disability in grade VIII. This study uses a cycle, in each cycle consists of planning, action, observation and reflection. Data collected through observation, and tests. Data analysis using qualitative and quantitative analysis. The results showed that, integrated thematic instructional, through contextual learning model, has changed performance of the students from cycle I to cycle II. The result of cycle I showed that the performance of the four students are R = 48%, T =54%, K =63% and S =59%. In cycle II, the performance of students increasing, R = 69%, T = 75%, K = 85%, and S = 81%. It could be concluded that integrated thematic instructional, through contextual learning model, effective for improving performance of students with mild intellectual disability.